Postęp techniczny w ujęciu literackim i refleksji humanistycznej. Współczesne wyzwania biotechnologii = Technical development in literature and humanistic reflection. Modern challenges of biotechnology - Olczak, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The presented paper aims to prove that the role of literature and humanities is to provoke reflections on responsibility for technical development. The author begins with the conceptualization of the technical development phenomenon and analyses it in terms of Hegelian theory adapted to modern times. Followingly, through the previously created theoretical frame, the author analyses the novels of Kazuo Ishiguro - "Never Let Me Go", and Ian McEwan - "Machines Like Me" searching for challenges of biotechnology identified by the authors. Both of them point out the fragility of human idea and conflicts that may occur when people start coexisting with posthumanous creations brought to life without proper ethical reflection before.
Keywords: postęp techniczny; Hegel, Georg Wilhelm Friedrich (filozof niemiecki; 1770-1831); posthumanizm; technical development; posthumanism